Efficacy of Current Practices for Pain Assessment in Premature Ventilated Infants in the NICU Exposed to a High Number of Pain-Associated Procedures. Issue 6 (November 2015) - Rohan, Annie J.
Abstract: Objective: To study infant factors, characteristics of pain scores, and analgesic practices associated with patient-days in the NICU with a high frequency of pain-associated procedures (defined as >10 pain-associated procedures in the day). Methods: This is a secondary analysis of data from a cross-sectional study that used medical record audits of premature, ventilated infants. The primary two-institution study yielded data for 196 patient-days. Data included 804 pain scores and 836 pain-associated procedures. Results: A high frequency of pain-associated procedures occurred in 8% of days at Site A and in 25% of days at Site B. Prevalence of days with high frequency of pain-associated procedures differed by institution, and was higher at the institution where infants were more mature at birth and had fewer surgical procedures. High frequency of pain-associated procedures was related to endotracheal intubation at both institutions. There were no elevated pain scores and no documented analgesic administrations on days with over 20 pain-associated procedures. Conclusions: High exposure to pain-associated procedures during a 24-hour period for a premature, ventilated infant is rarely associated with elevated pain scores or analgesic administration. Prevalence of days with high-procedural exposure at an institution appears to be closely related to use of invasive ventilation and to individual institutional practices. Examination and discussion of the daily frequency of pain-associated procedures for premature, ventilated infants (especially for those receiving invasive ventilation) may be helpful in developing approaches for attenuating the cumulative pain experience for these babies. Resources that are expended on regular pain reassessment documentation processes in the NICU may need to be reconsidered in light of the very low yield for clinical alterations in care in this setting. Abstract : Commonly used methods for pain assessment in premature ventilated infants may not accurately detect pain because a high number of pain-associated procedures was rarely associated with an elevated pain score. Resources that are expended on regular pain reassessment processes in the NICU may need to be reconsidered in light of the very low yield for clinical alterations in care in this setting. Better methods to more accurately assess and manage the infant pain experience are needed.